Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
how do you simplify, sin^2 x - 9/2cos x + 1 * 10cos x + 5/3sin x + 9? please help!?
2 Answers
- Anonymous9 years agoFavorite Answer
4+2=6...there, that's a lot simpler.
- MathBioMajorLv 79 years ago
First, do you recognize that sin² x - 9 is the difference of two squares? It factors into (sin x + 3)(sin x - 3). Also, we can factor the numerator and the denominator of the second fraction:
10cos x + 5 = 5(2cos x + 1)
3sin x + 9 = 3(sin x + 3).
After doing all the above, we can rewrite the original product like this:
[(sin x + 3)(sin x - 3) / (2cos x + 1)] • [5(2cos x + 1) / 3(sin x + 3)].
Notice now that (sin x + 3) in the numerator of the first fraction cancels its counterpart in the denominator of the second fraction. Also, we see that (2cos x + 1) in the denominator of the first fraction cancels its counterpart in the numerator of the second fraction. So, we are left with this:
(sin x - 3) • (5/3) = 5/3 (sin x - 3).
We can check the result by letting x be a convenient value. If the result above is correct, then when we plug x = 0° and x = 90° into the original expression and into the resulting simplified expression, the two values returned should be equal.
Let x = 0°, and x = 90°.
x = 0°, using original expression:
(sin² x - 9) / (2cos x + 1) • (10cos x + 5) / (3sin x + 9) =
[(0 - 9) / (2 + 1)] • [10(1) + 5 / 3(0) + 9] =
(-9 / 3) • (15 / 9) =
-3 • (15 / 9) =
-45 / 9 =
-5.
Now we use the resulting expression:
5/3 (sin x - 3) =
5/3 (0 - 3) =
(5/3) • (-3) =
5 • (-3/3) =
5 • (-1) =
-5.
Now let x = 90°, using the original expression:
(sin² x - 9) / (2cos x + 1) • (10cos x + 5) / (3sin x + 9) =
[(1 - 9) / (0 + 1)] • [(0 + 5) / (3 + 9)] =
(-8 / 1) • (5 / 12) =
-40 / 12 =
-10/3.
Now we use the simplified expression:
5/3 (sin x - 3) =
5/3 • (1 - 3) =
5/3 • (-2) =
-10/3.
Both values for x led to the same result in each expression, so the simplified answer is correct.